Buffalo before breakfast - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1999)
The magic tree house takes Jack and his sister Annie to the Great Plains where they learn about the life of the Lakota Indians.
"A Stepping Stone book.".
3.5
3-6
Keywords: Dakota Indians -- Fiction; Indians of North America -- Great Plains -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Dakota Indians -- Fiction; Magic -- Fiction; Native Americans -- Great Plains -- Fiction; Time travel -- Fiction; Tree houses -- Fiction